2022
DOI: 10.1038/s41586-022-04856-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antiviral susceptibility of SARS-CoV-2 Omicron BA.2

Abstract: The recent emergence of SARS-CoV-2 Omicron (B.1.1.529 lineage) variants possessing numerous mutations has raised concerns of decreased effectiveness of current vaccines, therapeutic monoclonal antibodies and antiviral drugs for COVID-19 against these variants 1,2 . The original Omicron lineage, BA.1, prevailed in many countries, but more recently, BA.2 has become dominant in at least 68 countries 3 . Here we evaluated the replicative ability and pathogenicity of authentic infectious BA.2 isolates in immunocomp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
170
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(193 citation statements)
references
References 68 publications
20
170
1
2
Order By: Relevance
“…21 Relying on evidence derived from experimental studies, viral replication of Omicron variant is inhibited in treated cell lines, and infection restricted in hamsters treated with oral antivirals. [7][8][9][10]22,23 It is postulated that Omicron is similarly sensitive to both drugs as previous variants, given most mutations of the Omicron variant are located around the spike protein, and those involving the target enzymes (RdRp and M pro , respectively) are distant from their active sites. [7][8][9]22,23 As illustrated in the current study conducted amid a pandemic wave of Omicron BA.2 variant, early initiation of nirmatrelvir/ritonavir (within five days of symptom onset) in community-dwelling COVID-19 patients was associated with significant reduction in the risks of all-cause mortality by 75% and hospitalization by 31% compared to non-use, whereas a more modest effect was observed with molnupiravir in lowering the mortality risk by 39%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Relying on evidence derived from experimental studies, viral replication of Omicron variant is inhibited in treated cell lines, and infection restricted in hamsters treated with oral antivirals. [7][8][9][10]22,23 It is postulated that Omicron is similarly sensitive to both drugs as previous variants, given most mutations of the Omicron variant are located around the spike protein, and those involving the target enzymes (RdRp and M pro , respectively) are distant from their active sites. [7][8][9]22,23 As illustrated in the current study conducted amid a pandemic wave of Omicron BA.2 variant, early initiation of nirmatrelvir/ritonavir (within five days of symptom onset) in community-dwelling COVID-19 patients was associated with significant reduction in the risks of all-cause mortality by 75% and hospitalization by 31% compared to non-use, whereas a more modest effect was observed with molnupiravir in lowering the mortality risk by 39%.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the original trials were carried out mostly during the Delta wave whereas effectiveness against Omicron and its subvariants can only be inferred from laboratory studies so far. 7-10 Here we assessed the clinical effectiveness of molnupiravir and nirmatrelvir/ritonavir among community-dwelling COVID-19 outpatients in Hong Kong during the Omicron BA.2.2 wave in January to May 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the beneficial effect of sotrovimab persists for other variant subtypes warrants further investigation [14][15][16][17]. For instance, the Omicron BA.2 sublineage was shown to exhibit marked resistance to sotrovimab in in vitro experiments [18,19], whereas an in vivo experiment found both molnupiravir and sotrovimab can restrict viral replication in the lungs of BA.2infected hamsters [20]. In addition, the patients included in this study are assumed to be only those who met the eligibility criteria made by NHS England [3], thus limiting further generalisation of our findings to people not in a known high-risk group.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Thus, a nasal vaccine that could induce highly cross-protective secretory IgA antibodies in the nasal mucosa, which is the gateway to respiratory infection, would be a more effective, reasonable vaccine candidate. It has been shown that the Omicron variant, which is currently prevalent around the world, could replicate more effectively in the bronchi than in the lungs, compared with other variants and the ancestor [4548]. Therefore, there is high chance that a nasal vaccine which could induce cross-protective IgA antibodies in the upper respiratory tract would be effective against the Omicron variant as well.…”
Section: Discussionmentioning
confidence: 99%